The Effect of Nutritional Education on Parental Knowledge of Balanced Nutrition in Children at Yayasan An - Nusyur Aeng Panas, Sumenep Madura - Ramadhan, Sasha Anggita; Widayani, Soraya Tri; Mahmudiono, Trias; Rakhmad, Amanda Fharadita Olivia; Hargiyanto, Ernadila Diasmarani; Permatasari, Fitiara Indah; Azzahra, Callista Naurah; Sahila, Nur; Atmaka, S.Gz, MPH, Dominikus Raditya; Febrianto, Eka Cahya; Astuti, Ratna Dwi Puji; Mulia, Shinta Arta; Pratiwi, Damai Arum; Nadhiroh, Siti Rahayu; Simangunsong, Tiara Tivany; Prameswari, Atika Anif; Ismail, Wan Ismahanisa; Mohd Noor, Mohamad Azhar bin; Mohamad Shariff, Mohamad Halim bin; Talib, Siti Salwa binti; Sabri, Nurhidayah binti; Abd Rahim, Nurul Ain binti; Tajuddin, Rosnida binti; Keah, Lee Siew; Mohd Fitri, Muhammad Firdaus bin; Rozlan, Muhammad Syahmi bin; Rao, Rishan Rao al Morgan; Mat Yasin, Azwa binti (Universitas Airlangga, 2024)
Parents play a vital role in shaping children's dietary habits, which are influenced by family behaviors, parental health literacy, and socio-economic status. Poor parental health literacy and low socio-economic status often lead to unhealthy child nutrition and lower physical activity. This study investigates the impact of nutritional education on parental knowledge at Yayasan An-Nusyur Aeng Panas, aiming to improve childhood nutrition in resource-limited settings. The research employed a pre-experimental design (one group pre-test post-test) to assess changes in parental knowledge after a 3-hour nutrition education session, delivered by a team of nutritionists from Indonesia and Malaysia. Data were collected from 27 parents of kindergarten students in Sumenep Madura in February 2024 through questionnaires. The results were analyzed using SPSS version 26 and the Wilcoxon Matched-Pairs Test. The findings revealed an increase in participants' knowledge, with a pre-test average score of 84.444 and a post-test average score of 86.667. However, the Wilcoxon test showed no statistically significant difference (p=0.439) between pre- and post-test scores. Despite the knowledge improvement after the education session, the difference was not significant. This suggests that while educational interventions can enhance awareness, further efforts may be required to achieve a measurable impact.